Identifying Project Delays in the Engineering Division of a Manufacturing Company: Using the Fishbone Diagram and Root Cause Approach - Setiawan, Enggal; Sulungbudi, Meylianti; Fitriani, Katlea (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Project delays are a common challenge in project management, especially in the engineering sector of the manufacturing industry. This study aims to identify the root causes of delays in production machinery procurement projects within the Engineering Division at PT XYZ, focusing on internal processes that affect project completion. The study uses Fishbone Diagram and Root Cause Analysis (RCA), which are effective tools to systematically uncover complex causal factors. The research is descriptive qualitative in nature, based on secondary data from 27 Project Status Reports (PSRs) from February 2022 to December 2023, categorized into six factors: Human, Machine, Method, Material, Measurement, and Environment. Fishbone analysis and 5 Whys were used to determine dominant and root causes. Finding show that delays are primarily caused by Method (25.4%), Machine (22.8%), and Human (21.1%) factors. Root causes include the lack of standardized design processes, limited machine precision for new design requirements, and delays in management decision-making due to incomplete technical information and multitasking among designers. To mitigate delays in future projects, PT XYZ is advised to establish a cross-functional planning team from the early stages, develop consistent SOPs for design, approval, and validation, and implement better human resource allocation through integrated project scheduling. These steps are expected to enhance project efficiency and accelerate technical decision-making processes.